Stress-related and reproductive hormones in hair from three north Pacific otariid species: Steller sea lions, California sea lions and northern fur seals. Issue 1 (8th September 2020) - Keogh, Mandy J; Gastaldi, Angela; Charapata, Patrick; Melin, Sharon; Fadely, Brian S
Abstract: Assessing the physiological impact of stressors in pinnipeds is logistically challenging, and many hormones are altered by capture and handling, limiting the utility of metabolically active tissues. Hair is increasingly being used to investigate stress-related and reproductive hormones in wildlife populations due to less-invasive collection methods, being metabolically inert once grown and containing multiple biomarkers of ecological interest. We validated enzyme immunoassays for measuring aldosterone, cortisol, corticosterone, and testosterone in lanugo (natal hair grown in utero ) samples collected from Steller sea lions ( Eumetopias jubatus ), California sea lions ( Zalophus californianus ), and northern fur seals ( Callorhinus ursinus ). We applied laboratory validation methods including recovery of added mass, parallelism and dilution linearity. We found no effects due to differences in alcohol- versus detergent-based cleaning methods. Further, there were no significant differences in hormone concentrations in hair samples collected immediately after the molt and the subsequent samples collected over 1 year, indicating steroid hormones are stable once deposited into pinniped hair. We found no sex differences in any hormone concentrations, likely due to the lanugo being grown in utero and influenced by maternal hormone concentrations. For Steller sea lion and California sea lion pups, we found hormone concentrations significantly differed between rookeries, which warrants future research. Hair provides a novel tissue to explore the intrinsic or extrinsic drivers behind hormone measurements in otariids, which can be paired with multiple health-related metrics to further investigate possible drivers of physiological stress.